Pengaruh Pembinaan dan Komunikasi Interpersonal Terhadap Komitmen Organisasi Pegawai Dinas Pendidikan Kabupaten Maluku Tengah - Abdul Hasan Patty; Eliana sari; Heru santosa (Jurnal Ilmiah Wahana Pendidikan, 2018)
The purpose of this study is seeking information about the effect of coaching and interpersonal communication on organizational commitment. the method of survey with quantitative approach in training civil servants in Central Maluku district. This study was conducted to seluruhu employees of Central Maluku district education offices by using a survey method and hypothesis testing path analysis is applied to 125 employees as a sample and selected by using the formula slovin. The results of this study are: (1) there is a direct effect of positive coaching to the organization's commitment. (2) there is a positive direct influence of interpersonal communication on organizational commitment. (3) there is a direct influence on the development of interpersonal communication.